Research on identification algorithm of oscillating current in DC incoming lines of metro - WANG Nanqing; QI Yu; XIN Lanyuan; SONG Jinchuan; TIAN Xingjun (机车电传动)
The paper presents a fault diagnosis and analysis algorithm centered on variational mode decomposition (VMD), sample entropy, and TOPSIS, to address the challenge of frequent misoperations of relay protection systems triggered by oscillating current in the incoming lines of metro traction power supply systems. Using a real-time digital simulation experimental platform, the improved incoming line protection algorithm was compared with traditional reverse current protection algorithms in the application scenario of metro relay protection devices. The experimental analysis verified the practicality and effectiveness of the proposed approach in engineering applications. The study findings highlight the algorithm’s capacity in identifying special oscillating current in DC incoming lines, offering a valuable means to enhance relay protection reliability.